Womanliness as Masquerade: Tracing Luce Irigaray’s Theory in Angela Carter’s Nights at the Circus - Sümbül, Yiğit (Journal of History Culture and Art Research, 2015)
Womanliness as Masquerade: Tracing Luce Irigaray’s Theory in Angela Carter’s Nights at the Circus Abstract Published in 1977 with a great deal of controversy within European feminist circles, Luce Irigaray’s This Sex Which Is Not One presents the author’s commentary on the modern phallocentric culture, commodification of women and their counteraction disguised within the very patriarchal structures. Irigaray, for instance, views womanliness and female submissiveness as a strategy that women have always made use of in order to develop a much more unfettered self behind such masks. Women masquerade as objects to be consumed to achieve a freer voice from the patriarchal discourse and to establish themselves as the ultimate subjects of a never-ending cultural exchange. Irigaray’s views on female strategies such as masquerade and performativity are applicable to a feminist reading of Angela Carter’s famous postmodern novel, Nights at the Circus (1984), which critiques the patriarchal ideology with its suggestion of a New Woman. Fevvers, the protagonist of the novel, imprisons the male voice in the novel behind the invisible cage of her own world of performances and uses her womanliness to suppress the male willpower to the degree of self-submission. In this respect, this study argues that Carter’s generation of Fevvers as the New Woman is reminiscent of what Irigaray theorizes in her above article with respect to questions like womanliness, masquerade and performativity.